1997
DOI: 10.1093/infdis/175.2.458
|View full text |Cite
|
Sign up to set email alerts
|

An ELISA for Detection of Antibodies to the E2 Protein of GB Virus C

Abstract: An ELISA was developed for detection of antibodies to GB virus C (GBV-C) using a recombinant E2 protein expressed in CHO cells. Seroconversion to anti-E2 positivity was noted among several persons infected with GBV-C RNA-positive blood through transfusion. Of 6 blood recipients infected by GBV-C RNA-positive donors, 4 (67%) became anti-E2 positive and cleared their viremia. Thus, anti-E2 seroconversion is associated with viral clearance. The prevalence of antibodies to E2 was relatively low (3.0%-8.1%) in volu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

19
133
3
1

Year Published

1997
1997
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 172 publications
(156 citation statements)
references
References 16 publications
19
133
3
1
Order By: Relevance
“…Satisfactory results have been obtained using Enzyme Immuno Assay (EIA) based on recombinant E2 protein expressed on Chinese Hamster Ovarian (CHO) cell. 8,11 HGV is transmitted by parenteral 12 , sexual 13 , and vertical 14 routes. Depending on the route of transmission of HGV, various risk groups including intravenous drug users (IDUs), commercial sex workers (CSW), multiply transfused patients (MTP), hemodialysis patients, anti-HCV positive patients, and anti-HIV positive patients were considered as study group in the present study.…”
Section: Resultmentioning
confidence: 99%
“…Satisfactory results have been obtained using Enzyme Immuno Assay (EIA) based on recombinant E2 protein expressed on Chinese Hamster Ovarian (CHO) cell. 8,11 HGV is transmitted by parenteral 12 , sexual 13 , and vertical 14 routes. Depending on the route of transmission of HGV, various risk groups including intravenous drug users (IDUs), commercial sex workers (CSW), multiply transfused patients (MTP), hemodialysis patients, anti-HCV positive patients, and anti-HIV positive patients were considered as study group in the present study.…”
Section: Resultmentioning
confidence: 99%
“…Thereby it was shown that most patients with posttransfusion GBV-C viremia who cleared the viral RNA became anti-E2 antibody (anti-E2) positive. 7,8 Additionally, GBV-C RNA and anti-E2 were almost mutually exclusive in patients' sera indicating that anti-E2 positivity correlated with GBV-C exposure and its clearance. 7,8 GBV-C has a parenteral route of transmission, and is frequently transmitted between intravenous drug abusers.…”
mentioning
confidence: 94%
“…7,8 Additionally, GBV-C RNA and anti-E2 were almost mutually exclusive in patients' sera indicating that anti-E2 positivity correlated with GBV-C exposure and its clearance. 7,8 GBV-C has a parenteral route of transmission, and is frequently transmitted between intravenous drug abusers. 9 Genomic sequence identity has been documented in matched pairs of blood donors and recipients.…”
mentioning
confidence: 94%
“…Since the end of 1996, an ELISA has been available for detection of antibodies to an envelope protein (anti-E2) of GBV-C (Tacke et al, 1997). Anti-E2 seroconversion is associated with viral clearance, suggesting that anti-E2 antibodies are a marker of a previous GBV-C infection (Dille et al, 1997). Therefore combining RT-PCR and ELISA should render a higher, more realistic, prevalence of GBV-C in various populations.…”
mentioning
confidence: 99%